2020
DOI: 10.1155/2020/8473253
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Module with Uniform Water Flow on Top Surface

Abstract: Though the solar photovoltaic (PV) module is used for power production, it usually works at high temperatures, decreasing its efficiency and therefore its output. So if an effective cooling method is to be implemented, it would reduce the heat from the solar PV module and increase its power production. Significant research in water cooling on both top and bottom surfaces of the PV module widen the scope for uniform cooling with constant module temperature throughout at any instant. In this work, unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Moreover, it should be noted that the higher level of efficiency reached by the module with the cooling mechanism is due to the higher amount of power generated by the module as seen from figure 5. The result of figure 6 agrees with earlier research by Govardhanan et al [28] which report that due to cooling, the output power and efficiency of the module was enhanced.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, it should be noted that the higher level of efficiency reached by the module with the cooling mechanism is due to the higher amount of power generated by the module as seen from figure 5. The result of figure 6 agrees with earlier research by Govardhanan et al [28] which report that due to cooling, the output power and efficiency of the module was enhanced.…”
Section: Resultssupporting
confidence: 90%
“…Their results revealed that the heat sink raised the open circuit voltage by 10%. While Govardhanan et al [28] experimentally investigated a PV module with uniform water flow on its surface for adequate cooling. Their report shows that due to cooling, the output power and efficiency of the module was enhanced by 15% and 14% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was established that cooling the panel was effective in improving its e ciency and conserving water. In a separate study [13], the photovoltaic panel was cooled by having three distinct ows of uniform water go over the top surface of the panel, which was supplied from the tank which was mounted on the top of the panel. It was concluded that cooling the PV module reduced the panel temperature by 30%, resulting in increased power production from 19 watts to 23 watts.…”
Section: Front Surface Coolingmentioning
confidence: 99%
“…As such, there are many cooling techniques available in the literature. For instance, a passive air-cooled system [13], [14], closed loop water cooling system [15], air-cooled system [16], and water sparkling system [17] as shown in Figure 3 respectively. Passive air-cooled system uses heat sinks as a heat transfer that can transfer the heat from a high thermal energy to a low temperature side and then cooled-up by the surrounding air.…”
Section: Figure 1 Pv Module Characteristic Curves Plotted For Different Temperaturesmentioning
confidence: 99%